PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DENGAN PEMBERIAN REWARD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS POKOK BAHASAN BENTUK-BENTUK PASAR KELAS VIII-A SMPN 1 MLANDINGAN - Dassucik Dassucik (STKIP PGRI SITUBONDO, 2015)
The low student’s learning activiesimpacted their learning outcomes. One of the influenced factor is learning model that applied by the teacher can not improved student’s learning activities. The goal of this research was improving student’s learning activity and learning outcomes through STAD learning model implementation in Economic especially in market form material Class VIII-AState Junior High School 1 Mlandingan on odd semester. According to the result of this study, student’s learning activities before conductedwas in low catagorie, whereas the classical mastery learning was 50%, which only 14 students complete in individual catagories. In the first cycle,student’s learning activities was 51,6%, and 88,8% in the second cycle. The improvement of learning outcomes in the first cycle is 75%, where 21 students pass by individual categorie. And the improvement of learning outcomes in the second cycle is 92,85%, where 26 students pass by individual categorie.